PENGGUNAAN SALURAN KOMUNIKASI DAN SIKAP PETANI TANAMAN HIAS TENTANG PROSPEK BISNIS ANTHURIUM (Anthurium sp) DI KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR - Octaviani Dian Sari; Supanggyo Supanggyo; Dwiningtyas Padmaningrum (Universitas Sebelas Maret, 2008)
Development of ornamental plant industry in Indonesia having good prospect. Anthurium is one of ornamental plant commodity which laboured many ornamental plant farmers to the effort business. In its bearing with activity business, ornamental plant farmers have to keep abreast of business always acces information in arround ornamental plant business of anthurium. In accesing information concerning anthurium, ornamental plant farmers can chosen and use various communication channel either though interpersonal channel and also mass media channel. The purpose ofthis research is to know communication channel any kind of exploited by ornamental plant business prospect anthurium, how level use o fcommunication channel by ornamental plant farmers to acces information about anthurium business prospect, how ornamental plant farmers attitude about anthurium business prospect, and how ornamental plant farmers attitude distribution about anthurium business prospect to the each type use communication channel. This research used descriptive method with survey technique. Research location is chosen intentionally in Ngargoyoso sub district Karanganyar regency. Consider that this sub district representing area broadly biggest anthurium development in Karanganyar regency. This sampling used random sampling that amount of80 respondents. To know the type and level use communications channel is used analysis the tables offrequency distribution. To measure attitude by using likert scale and to know attitude distribution to the each type use communications channel is used analysis tabulation traverse. The result ofthis research that used communications channel type is interpersonal channel and mass media channel. Level use of interpersonal communications channel many in the form of exploiting 3 source of information namely: friend, neighbour and farmer. Use of a/iance communications channel using many interpersonal channel with magazine. Ornamental plant farmer attitude in looking at anthurium business prospect that is most is positive. Farmer using interpersonal channel aliance and mass media which more behave compared to positive ofthem using just interpersonal communications channel.